POLA FRIEZE GROUP PADA GERAKAN TARI BUYUNG KUNINGAN - Lia Andriani; Arif Muchyidin (Department of Mathematics Education, Universitas Kuningan, 2020)
Buyung dance is rarely displayed and has begun to be unknown to the public. Also, children, today prefer foreign culture and dance. As a result, the existence of Buyung dance is only limited to recognition, without the benefits that can be felt. The absence of written guidelines in each of the Buyung dance movements is very interesting for researchers to analyze the relationship of the Buyung dance movements with mathematics. This type of research used in this study is qualitative research. In qualitative research, the instrument is the researcher himself and cannot be replaced by others. Data collection techniques used in this study through the method of observation, interviews, and documentation. Every hand movement of the dancers and movements between dancers to one another makes the movements of the dances neat and attractive following the Frieze Group, with four frieze patterns found in the dances of the pitchers.